Formalization of Banking Supervision 19th-20th Centuries - Hotori, Eiji (Springer Nature, 2022)
This open access book is the first attempt to elaborate the formalization phase of banking supervision in eight developed countries-USA, Japan, Sweden, Germany, Switzerland, Belgium, France, and UK. This innovative study in the field of banking supervision history identifies why national histories of banking supervision share similarities, but also remain different and are heavily path dependent. This book will be of great interest not only to financial/economic historians but also to general readers interested in banking supervision, i.e., students, bankers, supervisors, and international officials.